The Innovativeness of the Economies of European Union Candidate Countries – an Assessment of Their Innovation Gap in Relation to the EU Average - Dworak, Edyta (Comparative Economic Research. Central and Eastern Europe, 2024)
Innovation is nowadays seen as an essential success factor in achieving economic prosperity and competing in markets. It is one of the most important determinants of the competitive process throughout the world, helping economies catch up with developing and changing technologies while revealing those countries’ innovation perspectives. The article assesses the innovativeness of the economies of selected European Union (EU) candidate countries based on the Summary Innovation Index (SII). It also estimates the innovation gap between these countries and the EU average of the SII between 2015 and 2022. The analysis is limited to Türkiye, Serbia, Albania, Montenegro, North Macedonia, Bosnia and Herzegovina, and Ukraine due to the availability of data that describes the SII. It provided for all the countries surveyed in the European Innovation Scoreboards, i.e., the reports of the European Commission, only from 2015. The presented analysis is based on a research hypothesis that suggests that the surveyed countries are characterized by a lower level of innovativeness of economies than the EU average, and therefore, they show an innovation gap compared to the average for EU countries in the analyzed period. The results of the analysis confirm this hypothesis – between 2015 and 2022, the economies of all the examined candidate countries recorded a lower level of innovativeness than the EU average. They showed a lower level of the SII than the EU average, and therefore, all these countries demonstrated an innovation gap compared to the EU average. Recommendations for increasing the innovativeness of those economies are formulated separately in the conclusions. The article reviews the literature on the innovation and innovativeness of economies and the innovation gap. Descriptive analysis, statistical data analysis, and comparative analysis methods are applied, and statistical data from the European Innovation Scoreboard 2022 are used. The value added of the article lies in its comparison of the level of innovativeness of the economies of selected EU candidate countries to the EU average, as well as its estimation of the innovation gap between these countries and the EU average.